2017
DOI: 10.4236/health.2017.93031
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Daily and Occasional Smoking and Quitting in Irish University Students

Abstract: Knowledge of student smoking behaviors and attitudes was sought to inform a proposal to implement a smoke-free university campus. This study assessed prevalence of student smoking and quitting behaviors and associated demographic, contextual and attitudinal factors. A cross-sectional design using a convenience sample on a single university site was utilized. Data were collected by anonymous self-administered questionnaires and analyzed using bivariate and multivariable logistic models comparing smokers and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…The previous survey conducted in 2013 [5] reported an occasional smoking prevalence of 12%. Offering a social smoking option in our survey may have prompted participants to identify as social smokers rather than non-smokers which may in part explain the much higher prevalence.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The previous survey conducted in 2013 [5] reported an occasional smoking prevalence of 12%. Offering a social smoking option in our survey may have prompted participants to identify as social smokers rather than non-smokers which may in part explain the much higher prevalence.…”
Section: Discussionmentioning
confidence: 93%
“…Its aim is to achieve the national Tobacco Free Ireland goal of a smoking prevalence of less than 5% among students and staff [4]. A 2013 survey of daily and occasional smoking in Trinity, established that occasional, rather than daily smoking is more prevalent among Irish university students [5].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, before changes were made to the physical space, baseline data were collected on smoking prevalence [29]. About 19% of students smoked; 12% occasionally (non-daily) and 7% daily.…”
Section: Was the Characteristic Of The Ll Useful To This University?mentioning
confidence: 99%
“…A Tobacco Policy Committee which included the authors of this paper was established. Baseline data were collected on smoking prevalence [ 29 ] and a year-long consultation with over 10,000 engagements was conducted, consisting of online surveys, town hall meetings, working groups, and an undergraduate Students’ Union vote. The Students’ Union voted not to support the proposed policy [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…They use an aggregate of daily and occasional users instead of examining predictors for cessation attempts, for each group independently 24,27,28,30 . Studies have shown that there is a difference between daily and occasional tobacco users with regard to motivation 31 , perception 32 , and affect 33 . The objective of this study was to determine cessation attempts and related factors among daily SLT users.…”
Section: Introductionmentioning
confidence: 99%